Answer:
it is number 3 i actually did this one not even to long ago have a good day
Answer:
- Trinomials in the form can often be factored as the product of two binomials.
Step-by-step explanation:
As we know that a polynomial with three terms is said to be a trinomial.
Considering the trinomial of a form
As
a = 1
so
- Trinomials in the form can often be factored as the product of two binomials.
For example,
Therefore, Trinomials in the form can often be factored as the product of two binomials.
As we know :
Dividend = Divisor × Quotient ( taking remainder as 0 )
So, Quotient = Dividend ÷ Divisor
by using the above relation we can say :
therefore, correct option is C. t ÷ 23
Answer:
q+3/4r=p
Step-by-step explanation:
r=4/3(p-q)
Distribute the 4/3
r=4/3p-4/3q
Add 4/3q to each side
4/3q+r=4/3p
Multiply ALL variables by 3/4 (undoes the 4/3)
q+3/4r=p
Step-by-step explanation:
Solve for xsin3⁡x+cos3⁡x=1" role="presentation" style="margin: 0px; padding: 0px; border: 0px; font-style: normal; font-variant: inherit; font-weight: normal; font-stretch: inherit; line-height: normal; font-family: inherit; font-size: 15px; vertical-align: baseline; box-sizing: inherit; display: inline; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; position: relative;">xsin3x+cos3x=1xsin3x+cos3x=1
sin3⁡x+cos3⁡x=1(sin⁡x+cos⁡x)(sin2⁡x−sin⁡x⋅cos⁡x+cos2⁡x)=1(sin⁡x+cos⁡x)(1−sin⁡x⋅cos⁡x)=1" role="presentation" style="margin: 0px; padding: 0px; border: 0px; font-style: normal; font-variant: inherit; font-weight: normal; font-stretch: inherit; line-height: normal; font-family: inherit; font-size: 15px; vertical-align: baseline; box-sizing: inherit; display: inline; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; position: relative;">sin3x+cos3x=1(sinx+cosx)(sin2x−sinx⋅cosx+cos2x)=1(sinx+cosx)(1−sinx⋅cosx)=1